Experience of Midwives in Carrying Out Their Role of Assisting Pregnant Women - Diah Indriastuti; Ani Margawati; Nurullya Rachma; Tahiruddin Tahiruddin; Jeyma Ordonez Sahalul (LPPM STIKes Karya Kesehatan, 2021)
Abstract. Maternal mortality is often caused by a lack of support which causes problems during pregnancy and delivery that tend to be resolved late. Midwives have a role in implementing assistance and monitoring of maternal and child health. The purpose of this study was to obtain a description of the assistance of pregnant women by midwives in carrying out their roles. This research is a qualitative study with a phenomenological approach involving 5 midwives and 1 public health worker. The results of this study indicate 7 themes including implementers, managers, educators, counselors, collaborators, advocators, and midwifery care. The theme description explains that midwives can carry out their roles well, but there are obstacles during implementation and require support from various parties for cooperation